Enhance crashworthiness of composite structures using gradient honeycomb material. Issue 5 (3rd September 2018) - Zhang, Yong; Xu, Xiang; Lu, Minghao; Hu, Zhongwei; Ge, Pingzheng
ABSTRACT: Lightweight cellular materials can effectively improve the crashworthiness of thin-walled structures. To further investigate the potential of honeycomb-filled thin-walled structures, this paper proposed a novel functionally graded honeycomb (FGH) as filler. First, the finite element model of the functionally graded honeycomb-filled tube (FGHT) is established and validated via experimental results. Then, the key factors of FGHT for crashworthiness are identified. The results show that gradient pattern is critical to the crushing response. As for the overall energy absorption capability, we thoroughly examined the effects of gradient exponent n and the thickness range of honeycomb shells. Next, we conducted single and multi-objective optimisation, adopting genetic algorithm (GA) and non-dominated sorting genetic algorithm (NSGA-II), to seek the parameters that deliver overall crashworthiness performance. The Kriging surrogate metamodel was established to formulate specific energy absorption (SEA) and peak crushing force (PCF) in relation to the key parameters. The single objective optimisation revealed that, provided the same PCF, the SEA of FGHT is always higher than uniform honeycomb filled tube (UHFT); the Pareto front obtained from multi-objective optimisation also indicate that FGHT is generally more efficient than UHFT. This paper gives insights on the honeycomb-filled materials to achieve maximum crashworthiness performance.